Method for evaluating the displacement response of RC beams subjected to close-in explosion using modified SDOF model. (15th February 2018) - Nagata, M.; Beppu, M.; Ichino, H.; Takahashi, J.
Highlights: Approximation formulae for distributions of peak pressure and impulse are proposed. The formulae reproduce the test data of peak pressure and impulse adequately. A modified SDOF model considering the blast load distribution is proposed. This model effectively evaluates the response of RC beam by close-in explosion. Abstract: This study proposes a method for evaluating the displacement response of RC beams using the equivalent single-degree-of-freedom (SDOF) model considering a close-in blast load distribution. First, to examine the spatial distributions of the peak overpressure and impulse in a close-in explosion, explosion tests were conducted with C-4 explosives at scaled distances of 3.0–0.15 m/kg 1/3 . Approximation formulae for the spatial distributions of peak overpressure and impulse were proposed as functions of explosive mass, stand-off distance, and target member length. The peak overpressure and impulse estimated by the approximation formulae reproduced the test data adequately. Secondly, close-in explosion tests on RC beams using 110, 160, and 250 g C-4 explosives at a scaled distance of 0.20 m/kg 1/3 were conducted to examine the failure states of the RC beams. The modified SDOF model considering blast load distribution owing to close-in explosion was proposed. The proposed SDOF model effectively evaluated the displacement response of the RC beam subjected to the close-in explosive load, while the experimental results were marginally overestimated.